Synchronous meetings, community of inquiry, COVID-19, and online graduate teacher education. Issue 2 (18th May 2021) - Oyarzun, Beth; Hancock, Charlotte; Salas, Spencer; Martin, Florence
Abstract: With the arrival of the COVID-19 pandemic in March 2020, teacher colleges across the country suddenly shifted to online. In many cases, faculty, wary of shortchanging students of a meaningful learning experience, leveraged synchronous meetings as a way of compensating for the abrupt removal of face-to-face (F2F) interactions. This mixed-methods self-study explored advanced licensure candidates' perceptions of developing a Community of Inquiry (COI) across three sections of a Spring 2020 online course taught by the same instructor. This course was fashioned as a literature circle about immigrant communities and K-12 schools. In one section, five one-hour synchronous meetings punctuated the shared readings of five book-length ethnographies. The other two sections remained completely asynchronous. Sixty-nine students across the three courses were electronically surveyed at the close of the semester. Fifteen students were subsequently interviewed as an additional layer of data collection. Survey analysis indicated that monthly synchronous meetings did not significantly impact students' perceptions of COI development. Follow-up interviews provided further insights into methods that students perceived as essential for advancing teaching, cognitive, and social presences. We conclude with broad and specific recommendations for better practices and future research for COI in graduate teacher education online coursework in and beyond COVID-19.